Efeitos toxicológicos da nanopartícula de dióxido de titânio (TiO2) utilizando modelos experimentais in vitro e in vivo - Fattori, Ana Carolina Maragno (2023)
The advent of nanotechnology and its applications in diverse areas is due to the increase in the physical and chemical properties of nanoparticles because of their nanometric scale. However, these new characteristics can trigger biological effects that harm health and the environment, highlighting the need to assess the safety of using these nanomaterials. Therefore, this study analyzed the toxicological effects of titanium dioxide nanoparticles (TiO2 NP) functionalized with sodium carboxylate (-COO-Na+), of interest to the oil industry, using in vitro and in vivo models. The physicochemical characterization of the TiO2 NP was carried out using Dynamic Light Scattering (DLS), determining its hydrodynamic size, zeta potential and polydispersity index (PdI), Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR) and High-Resolution Scanning Electron Microscopy (SEM-FEG). For the in vitro model, the LA-9 fibroblast lineage was used and cytotoxicity was evaluated for the concentrations of 250, 150 and 50 μg/mL using the cell viability assay (MTT) and cell morphology analysis after exposure to TiO2 NP for 24, 48 and 72 hours. After exposure to TiO2 NP for 24 hours, intracellular production of Reactive Oxygen Species (ROS), production of cytokines IL-6 and TNF in the cell supernatant by ELISA and cell death by flow cytometry were also evaluated, as well as clonogenic survival 7 days after exposure. In the in vivo model, Balb/c mice were exposed intranasally to TiO2 NP (500, 250, 100 and 50 μg/animal) in 4 doses over 14 days. Throughout the exposure period, the animals' feed and water intake and weight variation were assessed. Subsequently, leukocyte levels were analyzed in the blood, bronchoalveolar lavage (BAL) and peritoneal cavity lavage (PCL), quantification of cytokines (INF-ɤ, TNF, IL-6 and IL-10) in plasma and BAL and IgE antibody in BAL by ELISA, evaluation of liver function (TGO/TGP), weighing of the lungs and histological analysis of the organs (brain, lungs, heart, liver, spleen and kidneys). Our results showed that NP TiO2 is functionalized with sodium carboxylate ligands and suggests that it has an anatase crystalline form, as well as heterogeneous dispersion and a hydrodynamic size of around 3.5 nm in water and 2.96 nm in PBS, increasing to 7.62 nm in DMEM medium due to the agglomeration process. For the LA-9 fibroblast cell line, there was a reduction in cell viability (250 and 150 μg/mL) dose and time-dependent as well as oxidative stress and cell death by apoptosis (150 μg/mL). For the 150 μg/mL concentration there was a possible cell recovery after the NP was removed. In the in vivo model, NP generated histopathological changes in the brain, lungs, liver and kidneys of Balb/c mice after intranasal exposure with 4 doses over a period of 14 days. No changes were observed in the other parameters evaluated, with the exception of an increase in TGO at a concentration of 250 μg. The results of this study showed that NP TiO2 functionalized with sodium carboxylate has cytotoxicity for the LA-9 fibroblast line and toxicity with histopathological alterations for the brain, lung, liver and kidneys in Balb/c mice, contributing to knowledge about the effects of this NP TiO2 in in vitro and in vivo models. It is also interesting to analyze long-term exposure in order to determine the safety of using this nanomaterial.